Organizational identification, commitment and orientations of professional military personnel - Todorović, Dušan; Čabarkapa, Milanko Dmitrov; Tošić-Radev, Milica; Miladinović, Ines (Vojnosanitetski pregled, 2017)
Background/Aim. All military organizations seek such employees who will advocate for the organization’s mission and act responsibly in the direction of achieving the objectives of operational and working groups to which they belong. Accordingly, the primary task of the military organization management is not only the cultivation of the members who would be committed to the organization, but also the officers and soldiers who identify with the organizational mission. The aim of this study was to examine differences in organizational identification, commitment to the organization and organizational orientations of the professional military personnel and employees in service and administrative activities. Methods. The research sample consisted of 450 respondents, of whom 150 were professional soldiers, 150 civilian employees in the service sector and 150 employees in the civil sector in administration. For statistical analysis of the data, the analysis of variance and canonical discriminant analysis were used. Results. Professional military personnel was characterized by a high degree of both organizational commitment and organizational identification, compared with employees in the civil sector - service and administrative activities. Through the process of canonical discriminant analysis, it was found that the professional military personnel are different from the other personnel in the sense that they identify with their colleagues and they feel a high degree of loyalty to the military organization, as key aspects of organizational identification. In addition, professional military personnel have pronounced affective commitment to the organization. Conclusion. Human resources are the key and the essential factor of advantage in the context of strong competitiveness in the field of military defense’s reality. Given that they are more adaptable and flexible, compared with the technological and structural resources, a high degree of experienced similarity with the other members of the organization, pronounced loyalty and affective commitment to the organization, to a large extent guarantee new successes and the progress of the military organization.